(untitled) (Sociología y tecnociencia, 2023)
The tourism industry suffered a significant loss from the COVID-19 pandemic. However, in line with decreasing the COVID-19 impacts, recent tourism behavior may be the cause of a phenomenon called as overtourism. The aim of this study was to investigate the unique phenomena of overtourism in Indonesia after the COVID-19 pandemic through a social pyschological approach. By using a critical discourse analysis, this study finds that a negative emotion generated by the COVID-19 pandemic has led to “revenge tourism” caused by two years of isolation. After the transmission effect of COVID-19 is decreasing, people who experience psychological breakdown, vent their tourism interests simultaneously, which in turn causing overtourism. In the perspective of psychology, negative emotion that has been piled up during lockdown may be the reason of overtourism. Meanwhile, overtourism also has negative social impact. From social-psychology perspective, place attachment is one of the basic needs in all human. When the control over their environment was disrupted, this may lead to many problems. Uncontrolled overtourism causes environmental damage and reducing the quality of tourism. Thus, this study suggests that the government and stakeholders collaborate to mitigate tourism disasters to prevent the threat of overtourism to tourism sustainability.